2012
DOI: 10.1007/s00535-012-0681-1
|View full text |Cite
|
Sign up to set email alerts
|

Peptic ulcers after the Great East Japan earthquake and tsunami: possible existence of psychosocial stress ulcers in humans

Abstract: In addition to the increased incidence of peptic ulcers, compositional changes in the disease were observed after the Great East Japan earthquake. The significant increase in the proportion of non-H. pylori and non-NSAID ulcers after the earthquake indicated that psychological stress alone induced peptic ulcers in humans independently of H. pylori infection and NSAID intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 34 publications
4
47
1
2
Order By: Relevance
“…Instead, our resilience measure captured susceptibility to stressful exposures and the results indicate an independent association between stress resilience and subsequent PUD risk. Sub-analysis in our study showed a higher magnitude association of stress resilience with gastric ulcers, consistent with the results from the study by Kanno et al 10 where psychological stress was more notably associated with gastric than duodenal ulcers. We can only speculate on the reasons for this, but animal studies may suggest that exposure to stress can affect the stomach as 10 it activates the HPA axis and influences mast cells in the stomach to release histamine 4, 10 and other chemical mediators, such as proteases.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Instead, our resilience measure captured susceptibility to stressful exposures and the results indicate an independent association between stress resilience and subsequent PUD risk. Sub-analysis in our study showed a higher magnitude association of stress resilience with gastric ulcers, consistent with the results from the study by Kanno et al 10 where psychological stress was more notably associated with gastric than duodenal ulcers. We can only speculate on the reasons for this, but animal studies may suggest that exposure to stress can affect the stomach as 10 it activates the HPA axis and influences mast cells in the stomach to release histamine 4, 10 and other chemical mediators, such as proteases.…”
Section: Discussionsupporting
confidence: 93%
“…Sub-analysis in our study showed a higher magnitude association of stress resilience with gastric ulcers, consistent with the results from the study by Kanno et al 10 where psychological stress was more notably associated with gastric than duodenal ulcers. We can only speculate on the reasons for this, but animal studies may suggest that exposure to stress can affect the stomach as 10 it activates the HPA axis and influences mast cells in the stomach to release histamine 4, 10 and other chemical mediators, such as proteases. These mediators trigger acid production increasing gastric ulcer risk, 10 as acid damage is one of the mechanisms that causes gastric ulcers; 4 but critically, mediators such as proteases cause deterioration of the gastric mucosa and thus susceptibility.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have shown that disaster-related psychological stress could have induced several physical and mental disorders (Kanno et al 2013;Tsuboi et al 2014;Hasegawa et al 2015), but mental health care for all victims seems to be insufficient. In fact, it is still difficult to know the number of people in Soso who are now suffering from post-traumatic stress disorder or other mental disorders caused by the disaster, because of the scarcity of mental health specialists.…”
Section: Commentarymentioning
confidence: 99%